Zoonotic Transmission of Campylobacter jejuni to Caretakers From Sick Pen Calves Carrying a Mixed Population of Strains With and Without Guillain Barré Syndrome-Associated Lipooligosaccharide Loci - St. Charles, Jessica L.; Brooks, Phillip T.; Bell, Julia A.; Ahmed, Husnain; Van Allen, Mia; Manning, Shannon D.; Mansfield, Linda S. (Frontiers in Microbiology, 2022)
Campylobacter jejuni is a leading cause of foodborne gastroenteritis that may trigger acute autoimmune sequelae including Guillain Barré Syndrome. Onset of neuromuscular paralysis is associated with exposure to C. jejuni lipooligosaccharide (LOS) classes A, B, C, D and E that mimic and evoke antibodies against gangliosides on myelin and axons of peripheral nerves. Family members managing a Michigan dairy operation reported recurring C. jejuni gastroenteritis. Because dairy cattle are known to shed C. jejuni, we hypothesized that calves in the sick pen were the source of human infections. Fecal samples were obtained from twenty-five randomly selected calves, one dog, and five family members and cultured for Campylobacter. C. jejuni isolates were obtained from thirteen calves and one asymptomatic family member; C. coli from two calves, and C. hyointestinalis from two calves. The dog had no Campylobacter. Some calves had diarrhea; most were clinically normal. Typing of lipooligosaccharide biosynthetic loci showed that eight calf C. jejuni isolates fell into classes A, B and C. Two calf isolates and the human isolate possessed LOS class E, associated mainly with enteric disease and rarely with GBS. Multi-locus sequence typing, porA and flaA typing, and whole genome comparisons of the thirteen C. jejuni isolates indicated that two calf strains and the human isolate were closely related, indicating zoonotic transmission. Whole-genome comparisons revealed that isolates differed in virulence gene content, particularly in loci encoding biosynthesis of surface structures. Family members experienced diarrheal illness repeatedly over two years, yet none experienced GBS despite exposure to calves carrying C. jejuni with LOS known to elicit antiganglioside autoantibodies.